Advances in growth curve and structural equation modeling : topics from the Indian Statistical Institute on the 125th birth anniversary of PC Mahalanobis /: topics from the Indian Statistical Institute on the 125th birth anniversary of PC Mahalanobis. ([2018]) - Unknown
No abstract available